Introducing and validating DramaZoom as a teaching tool for diverse student populations - Carvalho, Helena; Halpin, Patricia A.; Scholz-Morris, Elke; Carvalho, Rosa de; Contaifer, Daniel (Advances in physiology education, 2025)
DramaZoom is a teaching tool paired with a pretest to activate memory. It promotes learning for both medical students and undergraduate students with different majors in the study cohort. DramaZoom creates an opportunity for a fun learning experience that promotes knowledge gain in physiology regardless of whether the teaching setting is face to face or completely virtual. Future research will be done to investigate the long-term retention of content. Dramatization, a teaching method where each student acts out or mimics a cell or body parts while the entire group represents the physiological process was adapted to produce original teaching videos paired with a pretest that activates memory and a posttest to prevent misconceptions. Three physiology instructors collaborated on Zoom to create six DramaZoom videos (Dramatization via Zoom) focused on hormone signaling with negative feedback in different contexts. In these videos, each instructor personalizes a different part of an organ system or a physiological process, which allows the visualization of complex concepts in endocrinology. DramaZoom videos utilize theater, personification, and humor to represent physiological processes in a fun and creative way that facilitates students to learn and remember the content. Our goal was to introduce DramaZoom videos as an original teaching tool and present evidence of its efficacy on student learning. We analyzed the impact of DramaZoom videos on students’ knowledge acquisition at three distinct levels (1st year medical students, 3rd and 4th year undergraduate science students, and 1st year undergraduate nursing students) and investigated whether the mode of delivery of the videos (face to face during regular classroom teaching or asynchronous in a virtual classroom) affected student learning. Our data show that knowledge in all three student groups improved significantly after viewing DramaZoom videos independently of the mode of delivery. Our data indicate that DramaZoom videos combined with memory activation due to the pretest are an effective tool to instruct this cohort of students regardless of level and delivery mode. NEW & NOTEWORTHY DramaZoom is a teaching tool paired with a pretest to activate memory. It promotes learning for both medical students and undergraduate students with different majors in the study cohort. DramaZoom creates an opportunity for a fun learning experience that promotes knowledge gain in physiology regardless of whether the teaching setting is face to face or completely virtual. Future research will be done to investigate the long-term retention of content.